“Por que Vossa Alteza he ho próprio rey e senhor nosso”: gênero e poder nas representações e práticas políticas durante a regência de D. Catarina de Áustria (1557-1562) - Santos, Giovanna Aparecida Schittini dos (2019)
This research aims to analyze, from the perspective of gender category, the political performance of D. Catarina of Austria (1507-1578), Queen of Portugal, focusing mainly on the period of her regency (1557-1562) and is based on two concerns: the representations of the queen and the political practices of her legislative activity. Therefore, we present how she was represented as capable of government in two specular literature works, Francisco de Monzón ́s Libro Primero del Espejo de la Perfecta Princesa Cristiana, and Dos privilegios & praerogativas q ho genero feminino tem por direito comum & ordenações do Reyno mais que ho genero masculino by Rui Gonçalves, written in the period before the regency. We also worked to understand other elements that composed the political imaginary involving her: the charitable practices towards religious and private institutions; the portrait commissioned by her, which we defend, was intended to communicate the image of a queen who already ruled even when King D. João III (1502-1557) was still alive; the king’s memory as a component to legitimate her regency and finally, the representations that expressed the criticism of her government, her Spanish origin and the way she raised her grandson, D. Sebastião (1554-1578). In addition, we analyzed her legal activity as a regent, and identified the magistrates who entered the great courts of the kingdom at the time she was in power, the ties between them and the queen and how they operated as a political support to her reign. Finally, we researched the acts approved during the regency, with special emphasis on those who pronounced about Justice and Treasury, the impact it intended to have and the symbolic meanings it had in building a new image of the queen regent.